AD, Volume 35, n° 4, 2010 - Full Issue - journal system (Africa Development, 2021)
Selected papers from the 12th CODESRIA General Assembly except the one written by Johannes Tabi Atemnkeng Contents Women Engagement with Power and Authority in Re-writing East Africa Lennox Odiemo-Munara ........................1 Géophilosophie et déterritorialisation chez Gilles Deleuze : esquisse d’une nouvelle citoyenneté dans l’espace public postnational Serge Bernard Emmanuel Aliana........................19 Public Spheres, Personal Papers, Pedagogical Practices: Ruth First’s Academic Postings to/from Dar es Salaam and Maputo Barbara Harlow .................................47 Économie solidaire et espace public en Afrique : le cas de la région de Marrakech Brahim Elmorchid ...............................69 Housing Cape Town’s Forgotten Dead: Conflict in the Post-apartheid Public Sphere Louise Green & Noëleen Murray ..................89 Le Parlement congolais post-élection dans le processus de construction de l’espace public : mythe ou réalité ? Célestin Tshimande Tukala .......................109 Behind the Curtains of State Power: Religious Groups and the Struggle for Ascendancy in Nigerian Public Institutions - A Critical Appraisal Nkolika E. Obianyo ........................141 Governing ‘Ethnicised’ Public Sphere: Insights from Nigeria Nkwachukwu Orji ........................165 Des cimetières lotis à Kisangani : exemple d’un débat occulte sur la gestion des espaces publics en RDC Roger Ekongo Ndemba .........................179 Internet and the Egyptian Public Sphere Omnia Mehanna ............................195 Household-level Social Capital in Cameroon and Children’s Schooling: A Gender Analysis Johannes Tabi Atemnkeng ....................211 Mise en scène de la culture et espace public au Sénégal Ndiouga Benga .............................237